1996
DOI: 10.1002/elan.1140080202
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy characterization of electrode materials in electrochemistry

Abstract: Ex situ and in situ STM characterization of the electrode materials, including HOPG, GC, Au, Pt and other electrodes, is briefly surveyed and critically evaluated. The relationship between the electrode activity and surface microtopography is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Both roughening and smoothing have been reported. More recently, potential-induced reconstructions have been revealed in extenso by STM (see, for instance, the review articles by Kolb, Gewirth and Niece, Li and Wang, and Moffat).…”
Section: Resultsmentioning
confidence: 99%
“…Both roughening and smoothing have been reported. More recently, potential-induced reconstructions have been revealed in extenso by STM (see, for instance, the review articles by Kolb, Gewirth and Niece, Li and Wang, and Moffat).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are also plenty of examples where specific area, or “total active surface area”, was used instead. In this case, the electrode surface was defined as a three-dimensional object, with significant surface roughness. ,,, For example, it was demonstrated that the amount of adsorbed material on the electrode surface depends on the electrode conditions (surface roughness).
1 AFM images (2.20 μm × 2.20 μm) show the characteristic surface morphology for different carbon electrode substrates: (a) Highly oriented pyrolitic graphite (HOPG), (b) Fractured vitreous carbon (FVC) and (c) Mechanically polished vitreous carbon (MPVC).
2 Cyclic voltammograms for the Ag(NH 3 ) 2 + deposition process obtained onto HOPG, FVC, and MPVC electrodes, from 10 -2 M Ag(NH 3 ) 2 + /1.6 M NH 3 , 1 M KNO 3 electrolyte solution.
…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the electrode surface was defined as a three-dimensional object, with significant surface roughness. 17,21,24,[36][37][38] For example, it was demonstrated that the amount of adsorbed material on the electrode surface depends on the electrode conditions (surface roughness).…”
Section: Resultsmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) provides an excellent tool for these studies, because it can operate in situ to examine the electrode/electrolyte interface. [15][16][17] Although electrode materials such as Pt, Au, and graphite have been largely investigated by STM, 15 its use to the study of metal oxides is not so frequent. 18 Investigations of SnO 2 -based materials by STM or atomic force microscopy (AFM) have been reported.…”
mentioning
confidence: 99%